Resilience and governance of dispersed sub-Saharan migration in Morocco: The case of the refuge-cities of Tiznit and Taza - El Arabi, Sofia (Frontiers in Political Science, 2022)
This article aims to contribute to the construction of theoretical and empirical milestones of the concept of urban resilience by applying it to the field of sub-Saharan migration geography in Morocco. Our analysis is based on participatory action research conducted between 2017 and 2020 with a cohort of 215 migrants dispersed by the Moroccan state from the northern border areas of the country and forcibly relocated to the peripheral cities of Tiznit (south) and Taza (northeast). These two territories, to which the state delegates de facto responsibility for receiving and assisting dispersed migrants, have been transformed into refuge-cities. By mobilizing a set of indicators, we present an operational definition of resilient urban governance of sub-Saharan migration. While exploring the link between resilience and local hospitable mobilizations, we highlight the processes underlying the construction of urban initiatives to host dispersed migrants. We show that the framework of urban resilience is revelatory of inclusive reception dynamics, of the autonomous agency, and the innovative capacity of refuge-cities in the core of a debordering process.